2021
DOI: 10.3390/toxins13120910
|View full text |Cite
|
Sign up to set email alerts
|

Aurintricarboxylic Acid Decreases RNA Toxicity in a C. elegans Model of Repeat Expansions

Abstract: Pathologic expansions of DNA nucleotide tandem repeats may generate toxic RNA that triggers disease phenotypes. RNA toxicity is the hallmark of multiple expansion repeat disorders, including myotonic dystrophy type 1 (DM1). To date, there are no available disease-modifying therapies for DM1. Our aim was to use drug repositioning to ameliorate the phenotype of affected individuals in a nematode model of DM1. As the RNA interference pathway plays a key role in mediating RNA toxicity, we investigated the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In previous work in C. elegans, we demonstrated that repeatderived siRNAs can target transcripts bearing endogenous CUG/ CAG repeats and induce disease symptoms through the RNAi machinery (Qawasmi et al, 2019;Braun et al, 2021;Braun et al, 2022). Knockdown of key components of the RNAi pathway resulted in the rescue of the disease phenotype.…”
Section: Discussionmentioning
confidence: 82%
“…In previous work in C. elegans, we demonstrated that repeatderived siRNAs can target transcripts bearing endogenous CUG/ CAG repeats and induce disease symptoms through the RNAi machinery (Qawasmi et al, 2019;Braun et al, 2021;Braun et al, 2022). Knockdown of key components of the RNAi pathway resulted in the rescue of the disease phenotype.…”
Section: Discussionmentioning
confidence: 82%